Inclusive education readiness in suburban Malaysian primary schools - Muhammad Afif Mohd Aris; Siti Faizah Zainal; Noor Asmina Mohd Rashid; Mohd Muslim Md Zalli; Mohd Ridhuan Mohd Jamil; Mazarul Hasan Mohamad Hanapi (International Journal of Evaluation and Research in Education (IJERE), 2026)
Inclusive education requires not only equitable placement of students with disabilities in mainstream schools, but also adequate structural support and positive stakeholder readiness. This study examined the readiness of sub-urban primary schools in Malaysia to implement inclusive education by focusing on school facilities, teachers’ perceptions, peer acceptance, and parents’ perceptions. A quantitative cross-sectional survey was conducted involving headmasters, teachers, students, and parents from five primary schools implementing inclusive education programs. Data were analyzed using descriptive statistics and Pearson correlation analysis. The findings showed that although several accessibility features were available, many essential facilities and specialized instructional supports remained limited. In contrast, teachers, students, and parents generally demonstrated positive perceptions of inclusive education. Teachers’ experience with disability and understanding of disability-related needs were also significantly associated with more positive perceptions. These findings reveal a structural–social gap in inclusive education readiness, in which supportive stakeholder attitudes coexist with incomplete infrastructural support. The study highlights the need to strengthen school facilities and sustain professional development to support more equitable and effective inclusive education in primary schools.